EFFORTS TO RESOLVE CASES OF DOMESTIC VIOLENCE AT THE WOMEN AND CHILDREN SERVICE UNIT (PPA UNIT) PRABUMULIH POLICE - Lutfiyah Aziyati; Ruben Achmad; Martini Martini (Universitas Labuhanbatu, 2024)
One type of violence against women is domestic violence (KDRT). Domestic violence is any act against someone, especially women, which results in physical, sexual, psychological misery or suffering, and/or domestic neglect, including threats to commit acts, coercion, or unlawful deprivation of liberty within the household. . This research is a form of empirical method research. Empirical research is based on primary data (results of research in the field). The formulation of the problem that will be studied is efforts to resolve cases of domestic violence (KDRT) in the women's and children's service unit (PPA unit) of the Prabumulih Police. The result was that the Prabumlih Police PPA Unit in its efforts to overcome acts of domestic violence (KDRT) in Prabumulih City, namely by carrying out two types of solutions, namely by using penal means or through criminal legal channels and outside legal channels or non-penal means. Keywords: domestic violence, efforts of women and children service units